Identification of Coral Reefs in Mamburit Waters, Sumenep Regency - Sawiya Sawiya; Mohammad Mahmudi; Guntur Guntur (Journal of Experimental Life Science)
This research was conducted in September to October 2013 in Mamburit Waters, Sumenep Regency. This study was aimed to assess the percentage of coral reefs and acknowkedge the type of the coral reefs. Coral reefs was observed with the Line Intercept (LIT) method laid parallel to the coastline in the depth of 3 m and 10 m in windward and leeward area. Total of 59.88% coral reefs lived in leeward area in 3 m depth includes in good category and the percentage of dead coral reefs and other fauna for 40.12%. In the 10 m depth, 69.19% live coral reefs include as medium category with percentage of dead coral reefs and other fauna for 30.81%. Winward location of 3 m depth has 68.38% live coral reefs in good category and percentage of dead coral reefs and other fauna for 31.62%. Whereas for 10 m depth, 40.86% of live coral reefs include as medium category with percentage of dead coral reefs and other fauna for 59.14 %.